Variation In Infestation And Factors Affecting Oviposition Of Mango Pulp Weevil, Sternochetus Frigidus (Fabr.) (Coleoptera:Curculionidae) On Mango Mangifera Indica In Northern Peninsular Malaysia - Mohd Sobri, Nor Shazuani (2014)

(untitled)
Potential threat of Mango Pulp Weevil (MPW) to Malaysian mango industry was investigated by examining infested fruits from various orchards and scattered trees in residential areas in selected places in the northern peninsular Malaysia. Higher infestation of MPW was recorded in Kedah (65%) followed by Penang (60%) and Perlis (45%) and 22% from these states suffered severe infestation. Sternochetus frigidus preferred mango cultivars Gajah (mean weevil per fruit = 6.4±5.86) better than Siku Raja (3.6±0.93), Chok Anan (3.0±0.98), Sala (2.8±0.60) and Siam (2.7±0.47). Potensi ancaman kumbang pengorek buah mangga kepada industri mangga Malaysia telah disiasat dengan memeriksa buah-buahan yang diserang oleh MPW dari pelbagai kebun serta pokok-pokok yang ditanam di kawasan perumahan, dari tempat-tempat terpilih di utara Semenanjung Malaysia. Serangan yang lebih tinggi oleh MPW dicatatkan di Kedah (65%) seterusnya Pulau Pinang (60%) dan Perlis (45%) dan 22% daripada ketiga-tiga negeri mengalami serangan yang teruk.